Anisotropic electrical and thermal magnetotransport in the magnetic semimetal GdPtBi - Schindler, Clemens; Galeski, Stanislaw; Schnelle, Walter; Wawrzynczak, Rafal; Abdel-Haq, Wajdi; Guin, Satya N.; Kroder, Johannes; Kumar, Nitesh; Fu, Chenguang; Borrmann, Horst; Shekhar, Chandra; Felser, Claudia; et al. (Physical Review B, 2020)
The half-Heusler rare-earth intermetallic GdPtBi has recently gained attention due to peculiar magnetotransport phenomena that have been associated with the possible existence of Weyl fermions, thought to arise from the crossings of spin-split conduction and valence bands. On the other hand, similar magnetotransport phenomena observed in other rare-earth intermetallics have often been attributed to the interaction of itinerant carriers with localized magnetic moments stemming from the 4f shell of the rare-earth element. In order to address the origin of the magnetotransport phenomena in GdPtBi, we performed a comprehensive study of the magnetization, electrical, and thermal magnetoresistivity on two single-crystalline GdPtBi samples. In addition, we performed an analysis of the Fermi surface via Shubnikov-de Haas oscillations in one of the samples and compared the results to ab initio band structure calculations. Our findings indicate that the electrical and thermal magnetotransport in GdPtBi cannot be solely explained by Weyl physics and is strongly influenced by the interaction of both itinerant charge carriers and phonons with localized magnetic Gd ions and possibly also paramagnetic impurities.
CRIS-Team Scopus Importer:2022-04-14